أثر تطبيق مبادئ الحوكمة الضريبية على جودة الأداء المحاسبي الضريبي (Comprehensive Journal of Science, 2025)
This study aims to examine the impact of applying tax governance principles on the quality of tax accounting performance. To achieve this objective, a questionnaire was developed by the researcher after verifying its validity and reliability, and then distributed to a sample of employees working in the tax administration within major cities and several affiliated offices. A random sample was selected from the study population, and a total of 120 questionnaires were distributed.The study employed the descriptive method for the theoretical framework and the analytical method for processing and analyzing the collected data. The Statistical Package for the Social Sciences (SPSS) was used to analyze the data and test the hypotheses through various statistical techniques, including Cronbach’s Alpha to measure the internal consistency and reliability of the questionnaire items, arithmetic means and standard deviations to assess the degree of agreement among the study variables, and the One Sample T-Test to determine the acceptance or rejection of the proposed hypotheses.The findings revealed a significant impact of applying tax governance principles on the quality of tax accounting performance at the Libyan Tax Authority. This result was confirmed by the respondents’ agreement, as reflected in the acceptance of the three hypotheses related to the application of governance principles in tax legislation, tax administration, and the tax community, all of which contribute to enhancing the quality of tax accounting performance.The study also presented several recommendations, the most important of which include the need to update tax legislation in alignment with tax governance requirements to improve and enhance the efficiency of tax accounting performance. Furthermore, the study emphasized the importance of integrating modern information technologies into tax collection processes and linking them to a unified system to promote fairness and transparency in taxation, as well as the necessity of training and developing tax personnel in the implementation of tax governance principles.
Keywords: Tax Governance Principles; Quality of Tax Accounting Performance; Efficiency of Tax Administration; Tax Compliance; Libyan Tax Legislation; Tax Transparency; Tax Information Systems